Amorphization in extreme deformation of the CrMnFeCoNi high-entropy alloy - Zhao, Shiteng; Li, Zezhou; Zhu, Chaoyi; Yang, Wen; Zhang, Zhouran; Armstrong, David E. J.; Grant, Patrick S.; Ritchie, Robert O.; Meyers, Marc A. (Science advances, 2021)
Extreme deformation of high-entropy alloys increases toughness by converting crystalline structures to amorphous zones. Ever-harsher service conditions in the future will call for materials with increasing ability to undergo deformation without sustaining damage while retaining high strength. Prime candidates for these conditions are certain high-entropy alloys (HEAs), which have extraordinary work-hardening ability and toughness. By subjecting the equiatomic CrMnFeCoNi HEA to severe plastic deformation through swaging followed by either quasi-static compression or dynamic deformation in shear, we observe a dense structure comprising stacking faults, twins, transformation from the face-centered cubic to the hexagonal close-packed structure, and, of particular note, amorphization. The coordinated propagation of stacking faults and twins along {111} planes generates high-deformation regions, which can reorganize into hexagonal packets; when the defect density in these regions reaches a critical level, they generate islands of amorphous material. These regions can have outstanding mechanical properties, which provide additional strengthening and/or toughening mechanisms to enhance the capability of these alloys to withstand extreme loading conditions.